2022
DOI: 10.1051/0004-6361/202142733
|View full text |Cite
|
Sign up to set email alerts
|

Constraining the radio properties of the z = 6.44 QSO VIK J2318−3113

Abstract: The recent detection of the quasi-stellar object (QSO) VIKING J231818.3−311346 (hereafter VIK J2318−3113) at redshift z = 6.44 in the Rapid ASKAP Continuum Survey (RACS) uncovered its radio-loud nature, making it one of the most distant known to date in this class. By using data from several radio surveys of the Galaxy And Mass Assembly 23h field and from a dedicated follow-up, we were able to constrain the radio spectrum of VIK J2318−3113 in the observed range ∼0.1–10 GHz. At high frequencies (0.888–5.5 GHz i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 84 publications
2
4
0
Order By: Relevance
“…This constrains the spectral index of the pc-scale feature to 𝛼 < −1.2, which is consistent with the value found for the kpc-scale radio emission [8]. Detailed analysis [8] showed that the radio emission of J2318−3113 likely originates from a recently formed quasar jet, as fitting both a curved (peaked) and a double power law model to the radio spectrum implies a young kinetic (∼ 500 yr) and radiative age (≲ 9 × 10 4 yr).…”
Section: Viking J23181835−3113463supporting
confidence: 89%
See 1 more Smart Citation
“…This constrains the spectral index of the pc-scale feature to 𝛼 < −1.2, which is consistent with the value found for the kpc-scale radio emission [8]. Detailed analysis [8] showed that the radio emission of J2318−3113 likely originates from a recently formed quasar jet, as fitting both a curved (peaked) and a double power law model to the radio spectrum implies a young kinetic (∼ 500 yr) and radiative age (≲ 9 × 10 4 yr).…”
Section: Viking J23181835−3113463supporting
confidence: 89%
“…The source VIKING J231818.35−311346.3 (J2318−3113) was identified as a quasar at redshift 𝑧 = 6.44 [1], and detected in the radio domain at 888 MHz in the Galaxy and Mass Assembly and Rapid ASKAP Continuum Surveys [7]. J2318−3113 was found to be a radio-loud (radio loudness parameter 𝑅 = 70, [7]) steep spectrum quasar, with a spectral index of 𝛼 = −1.24 between 888 MHz and 5.5 GHz ( [8], following the 𝑆 ∼ 𝜈 𝛼 convention, where 𝑆 is the flux density and 𝜈 is the frequency).…”
Section: Viking J23181835−3113463mentioning
confidence: 99%
“…5 image noise) was detected at 4.7 GHz [19]. This constrains the spectral index of the pc-scale feature to < −1.2, which is consistent with the value found for the kpc-scale radio emission [8]. These findings imply that the radio emission originates from a recently formed young quasar jet in the early Universe [19].…”
Section: Viking J23181835−3113463supporting
confidence: 88%
“…The source VIKING J231818.35−311346.3 (J2318−3113) was identified as a quasar at redshift = 6.44 [1], and detected in the radio domain at 888 MHz in the Galaxy and Mass Assembly and Rapid ASKAP Continuum Surveys [7]. J2318−3113 was found to be a radio-loud (radio loudness parameter = 70, [7]) steep spectrum quasar, with a spectral index of = −1.24 between 888 MHz and 5.5 GHz ( [8], following the ∼ convention, where is the flux density and is the frequency).…”
Section: Viking J23181835−3113463mentioning
confidence: 99%
“…The search for ultra-high-redshift radio-loud AGN has now progressed beyond z = 6. Radio-loud quasars have recently been identified near the end of the EoR (z ∼ 6.5): VIK J2318−3113 at z = 6.44 (Ighina et al 2021(Ighina et al , 2022) and P172+18 at z = 6.82 (Bañados et al 2021;Momjian et al 2021). In addition, Belladitta et al (2020) discovered PSO J0309+27 at z = 6.10; this radioloud source is the most distant known blazar.…”
Section: Introductionmentioning
confidence: 99%